Lipid Emulsion Infusion Rescues Dogs From Bupivacaine-Induced Cardiac Toxicity. Issue 3 (1st May 2003) - Weinberg, Guy; Ripper, Richard; Feinstein, Douglas L.; Hoffman, William
Abstract : Background and Objectives: We previously demonstrated in rats that intravenous infusion of a lipid emulsion increases survival in resuscitation from severe bupivacaine cardiac toxicity. The present studies were undertaken to determine if this method is similarly effective in a non-rodent model using a larger animal. Methods: Bupivacaine, 10 mg/kg, was administered intravenously over 10 seconds to fasted dogs under isoflurane general anesthesia. Resuscitation included 10 minutes of internal cardiac massage followed with either saline or 20% lipid infusion, administered as a 4-mL/kg bolus followed by continuous infusion at 0.5 mL/kg/min for 10 minutes. Electrocardiogram (EKG), arterial blood pressure (BP), and myocardial pH (pHm) and pO2 (pmO2) were continuously measured. Results: Survival after 10 minutes of unsuccessful cardiac massage was successful for all lipid-treated dogs (n = 6), but with no survivors in the saline controls (n = 6) ( P < .01). Hemodynamics, PmO2, and pHm were improved during resuscitation with lipid compared with saline treatment in which dogs did not recover. Conclusions: We found that infusing a lipid emulsion during resuscitation from bupivacaine-induced cardiac toxicity substantially improved hemodynamics, pmO2, and pHm and increased survival in dogs.